Learning Memorize Arabic Vocabulary with Hangman Games - Wijaya, Candra; Murdiono, Murdiono; Sarimov, Renat (Arabi : Journal of Arabic Studies, 2023)
The use of Hangman game media is based on the lack of Arabic language game media. This condition causes students to become bored and pay less attention to learning. The lack of game media supporting Arabic as the main language makes researchers use the Hangman game media. This study aims to see how efficiently the Hangman interactive game improves vocabulary memorization XI grade students. The pre-experimental method was adopted, in which the researcher conducted a pre- and post-test. The researcher utilized a simple random sampling procedure using a sample of 28 students in her study. The data gathering strategy employed observation and tests to determine the student knowledge level. The T Test is a method of data analysis. In this case, students' scores improved after they played the Hangman game. After playing the Hangman game, students can memorize 5-6 new vocabulary words on average. Which was possible to say that using Hangman games to improve students' vocabulary memorization is effective. The Hangman game can be used as the main medium of learning or inserted in making learning materials on powerpoint to make learning conditions more enjoyable.